Music Timing Differentiates Fatigue Perception and Performance during Isometric Strength Exercises: A Crossover Randomised Trial. - Tsz-Chun Poon, Eric; Wing Lam Kwan; Chi Ching Chow; King Chung Chan, Derwin (Journal of Sports Science & Medicine, 2024)
Music is well-known to elicit ergogenic effects on exercise performance; however, the moderating role of application timing remains unclear. This study examined the effects of the timing of music on fatigue perception and performance during isometric strength exercises. Using a within-subject, randomised crossover design, twelve recreationally active young adults performed two isometric strength tasks (plank-hold and wall-sit) in three separate conditions (MEE: music played during the entire exercise task; MDF: music played during fatigue alone; CON: no music). The total time to volitional exhaustion (TTE), time to the onset of fatigue perception (TFP), heart rate, and blood lactate responses were assessed during each trial. MEE resulted in a significantly longer TTE than CON in both the plank-hold (p < 0.05, d = 0.76) and wall-sit exercises (p < 0.05, d = 0.72), whereas MDF led to a significantly longer TTE than CON in wall-sit exercises alone (p < 0.05, d = 0.60). TFP was significantly longer in MEE than in CON in both the plank-hold (p < 0.05, d = 0.54) and wall-sit exercises (p < 0.05, d = 0.64). The music condition did not influence the heart rate or blood lactate changes in any of the trials. Our results suggest that listening to music during the entire exercise can delay the onset of fatigue perception in isometric strength tasks, whereas listening to music during fatigue has only a modest effect. Athletes and exercisers should consider extending music exposure throughout the entire exercise task to maximise performance benefits.